Analisis Pemberlakuan Surat Edaran Wali Kota Pekanbaru Nomor 77/SE/2024 tentang Pengelolaan Sampah Berbasis Masyarakat/Komunitas dan Retribusi Non-Tunai dalam Perspektif Good Governance - Betharia Pinarsita (International Forum of Researchers and Lecturers, 2026)
Waste management in Pekanbaru City has become a critical issue, with daily waste production reaching 800-1000 tons, necessitating professional handling. To address this, the Pekanbaru City Government issued Circular Letter (SE) Number 77/SE/2024 regarding Community-Based Waste Management and Non-Cash Retribution as a policy breakthrough for transparency and community participation. This research aims to analyze the legal validity of this Circular Letter within the local government system, identify implementation obstacles, and examine efforts to achieve Good Governance. This study employs a juridical-empirical or sociological approach, using purposive sampling to select informants, including Waste Management Institution (LPS) officers and RT/RW heads. Data were collected through interviews and literature reviews. The findings reveal that the Circular Letter serves as a valid policy rule (beleidsregel) derived from the Mayor's discretionary power (freies ermessen) to address urgent regional needs. However, field implementation faces significant challenges, including low public legal culture, digital literacy gaps regarding non-cash payments, and inadequate infrastructure. Efforts toward Good Governance are reflected in community participation through LPS empowerment and transparency via retribution modernization to prevent illegal levies. Nevertheless, the research suggests that the government should upgrade the policy's legal status to a Regional Regulation to provide stronger legal certainty and administrative stability. Effective socialization and infrastructure improvements are also essential to bridge the gap between policy objectives and community readiness in Pekanbaru's waste management system.